Causes and consequences of individual variation in the extent of post‐juvenile moult in the blue tit Cyanistes caeruleus (Passeriformes: Paridae). (6th June 2015) - Crates, Ross A.; Sheldon, Ben C.; Garroway, Colin J.
<x xml:space="preserve">Abstract</x> Moult, comprising the growth or replacement of feathers in birds, is an energetically demanding process. As a result, in many species, the extent of the post‐juvenile moult can vary substantially. However, the reasons underlying this variation remain poorly understood, and the potential life‐history consequences of variation in moult extent are even less clear. In the present study, we aimed to use individual‐specific data to identify factors affecting the extent of the post‐juvenile moult in a population of over 2500 blue tits Cyanistes caeruleus Linnaeus 1758, and to assess the consequences of individual variation in moult extent on reproduction in the first year of life. There was a substantial sex difference in post‐juvenile moult extent, with males moulting more extensively than females. Putative immigrant birds had moulted on average less than those born locally. However, there was little evidence of carry‐over effects of the natal environment on moult extent because we found no relationship between moult extent and fledging date or nestling mass. Evidence that moult extent, and hence feather brightness, affected subsequent reproductive success was limited. Moult extent had no effect on recruitment in males, although female recruits had moulted significantly less than nonbreeders. Because it was not influenced by features of the natal environment, moult extent may not be an honest signal of individual quality in C. caeruleus. As a result, the potential consequences of variation in moult extent for fitness are likely to be small.